Beyond the human - Garden communities in community gardens - Verena K. Fisch (Social Work & Society, 2023)
This paper contributes to the growing body of literature on ecosocial work that advocates for a refocus of the social work profession towards more-than-human environments and interconnectedness. One context in which the relationships between people and other-than-human beings become particularly concrete and tangible are community gardens. Based on five interviews with social workers in England, I examined practitioners' experience with ecosocial work in community gardens, prevalent human-centred perspectives on gardening activities, and the more-than-human relationships that emerge in garden settings. Using Bruce Morito's concept of thinking ecologically, I argue that from an ecosocial work perspective community gardens should not be instrumentalised solely for human benefits and reduced to the human communities they cultivate. Instead, ecosocial work needs to pay closer attention to the multispecies relationships emerging in garden settings.